Directory of services for technical assistance in shipping, ports, and multimodal transport to developing countries - United Nations Conference on Trade and Development ([New York] : United Nations, 1984)
The book examines shipping, ports, and multimodal transport to developing countries and provides necessary information that would enhance technical assistance to these countries.
Issued also in Arabic, French, and Spanish; original in English.
Includes bibliographical references: p. 8.
usc 21/02/2019
Loans
Keywords: Harbors--International cooperation; Shipping--International cooperation; Technical assistance; Developing countries